Legal Protection for Consumers Regarding the Absence of Labels Containing Product Information on Packaging - Putri, Dinae; Sulistyarini, Rachmi; Widyanti , Yenny Eta (International Journal of Business, Law, and Education, 2023)
This research is aimed at understanding and analysing the legal protection regarding the absence of product information labels on packaging. As legal protection for consumers is an important issue in the context of safeguarding consumer rights and interests, one frequently discussed aspect is the lack of product information labels on packaging. This disorderliness can pose various risks to consumers, such as difficulties in making informed purchasing decisions, financial loss, health, and safety concerns. This study adopts a Normative Juridical research approach. The analytical technique used in this research is descriptive analysis, examining various regulations and laws that govern consumer protection and product labelling. The research findings indicate that consumers have the right to obtain accurate, clear, and complete information about the products they intend to purchase or consume. The absence of product labelling on packaging can result in consumers' inability to make informed decisions. Therefore, various regulations and laws have been established to mandate businesses to provide accurate and complete information on product packaging. This research concludes that legal protection for consumers concerning the absence of product information labels on packaging is highly significant. Continuous efforts are required to enhance business compliance, effective law enforcement, as well as consumer education and awareness regarding the importance of obtaining accurate information before purchasing products.